Analisis Faktor-Faktor yang Mempengaruhi Produksi Padi di Sumatera Menggunakan Metode Regresi Linier - Mohammad Yusuf Nugroho; Nurmalitasari (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2023)
In research data must go through a processing process so that it can be used in the research. The data used must be valid to be able to produce an appropriate solution. This study aims to analyze the factors that influence rice production in paddy fields. The island of Sumatra has more than 50 percent of agricultural land in each province with the most dominant main food commodity being rice, while the remainder is corn, peanuts and sweet potatoes. Agricultural products in Sumatra are very vulnerable to climate change which can affect cropping patterns, planting time, production and yield quality. Climate change can have a negative impact on the production of these basic commodities. Moreover, an increase in the earth's temperature due to the impact of global warming which will affect the pattern of precipitation, evaporation, water runoff, soil moisture, and climate variations which are very fluctuating as a whole can threaten the success of agricultural production. Predictions of agricultural yields for food commodities are heavily influenced by climate change. The method used for analysis is Linear Regression and also uses the python library.